Why some firms train apprentices and many others do not - Wolter, Stefan C. [Verfasser]; Mühlemann, Samuel [Verfasser]; Schweri, Jürg [Verfasser] (My University, 2006)
"The latest study investigating the cost-benefit ratio of apprenticeship training for Swiss companies has shown that most apprentices offset the cost of their training during their apprenticeship on the basis of the productive contribution of the work they perform. Given this outcome, it is worth investigating why so many firms choose not to train apprentices. Maximum-likelihood selection models were used to estimate the net cost of training for firms without an apprenticeship programme. The models show, firstly, that non-training firms would incur significantly higher net cost during the apprenticeship period if they would switch to a training policy and, secondly, that this less favourable cost–benefit ratio is determined less by cost than by absence of benefit. For the apprenticeship system as such the results indicate that, as long as training regulations and the market situation permit a cost-effective training of apprentices, companies do not need specific labour market regulations or institutions to offer training posts. In this respect, the Swiss findings might be of interest for the ongoing German discussion about the expected repercussions of a more general labour market deregulation on the apprenticeship training system." (Autorenreferat, BIBB-Doku)
Vorab veröffentlicht als IZA DP No. 916 (October 2003): http://ftp.iza.org/dp916.pdf [Zugriff 3.5.2011]
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Kosten-Nutzen-Analyse; Ausbildungsverhalten; Ausbildungsbereitschaft; Empirische Untersuchung; Schweiz